2016
DOI: 10.1242/jeb.138610
|View full text |Cite
|
Sign up to set email alerts
|

The role of plantigrady and heel-strike in the mechanics and energetics of human walking with implications for the evolution of the human foot

Abstract: Human bipedal locomotion is characterized by a habitual heel-strike (HS) plantigrade gait, yet the significance of walking foot-posture is not well understood. To date, researchers have not fully investigated the costs of non-heel-strike (NHS) walking. Therefore, we examined walking speed, walk-to-run transition speed, estimated locomotor costs (lower limb muscle volume activated during walking), impact transient (rapid increase in ground force at touchdown) and effective limb length (ELL) in subjects (n=14) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 69 publications
(105 reference statements)
2
29
0
Order By: Relevance
“…This strategy distinguishes humans from other terrestrial bipeds (Usherwood et al, 2012), and may partly account for the relatively low metabolic cost of walking in humans (Biewener et al, 2004;Cunningham et al, 2010). Additionally, Webber and Raichlen (2016) demonstrated that use of a heel strike at the beginning of stance during plantigrade walking allows the center of pressure to roll forward under the foot during stance phase, effectively increasing stride length and improving human walking economy. Because great apes use plantigrade foot postures, we hypothesize that they also benefit from the advantages described above during bipedalism.…”
Section: Foot Strike and Collisionmentioning
confidence: 99%
See 4 more Smart Citations
“…This strategy distinguishes humans from other terrestrial bipeds (Usherwood et al, 2012), and may partly account for the relatively low metabolic cost of walking in humans (Biewener et al, 2004;Cunningham et al, 2010). Additionally, Webber and Raichlen (2016) demonstrated that use of a heel strike at the beginning of stance during plantigrade walking allows the center of pressure to roll forward under the foot during stance phase, effectively increasing stride length and improving human walking economy. Because great apes use plantigrade foot postures, we hypothesize that they also benefit from the advantages described above during bipedalism.…”
Section: Foot Strike and Collisionmentioning
confidence: 99%
“…The foot also displays a fully adducted hallux, but its first metatarsal is relatively short, and its cuboid and navicular bones are shaped similarly to those of African apes, suggesting a longitudinal arch that was only weakly developed or absent (Jungers et al, 2009b). These features do not preclude effective bipedal walking, as a long foot should reduce metabolic costs assuming the use of heel-strike plantigrady (Cunningham et al, 2010;Webber and Raichlen, 2016), and alternative mechanisms could have been utilized to stiffen the foot even in the absence of a longitudinal arch (Bates et al, 2013;Venkadesan et al, 2017 preprint). However, lacking a human-like longitudinal arch, H. floresiensis would have been unable to take advantage of significant elastic energy savings in its foot (Stearne et al, 2016), and its long toes would have required high muscle force production during running (Rolian et al, 2009).…”
Section: Box 1 the Odd Foot Of Homo Floresiensismentioning
confidence: 99%
See 3 more Smart Citations